Applied computational physics - Boudreau, Joseph F.; Swanson, Eric Scott (Oxford University Press, 2018)
A textbook that addresses a wide variety of problems in classical and quantum physics. Modern programming techniques are stressed throughout, along with the important topics of encapsulation, polymorphism, and object-oriented design. Scientific problems are physically motivated, solution strategies are developed, and explicit code is presented.